2022
DOI: 10.1002/nop2.1433
|View full text |Cite
|
Sign up to set email alerts
|

Expedited upskilling of intermediate care nurses to provide critical care during the COVID‐19 pandemic

Abstract: Aim Describe the strategy, efficacy and preferred mechanisms of training used to rapidly upskill intermediate care nursing staff to provide critical care during the COVID‐19 pandemic. Design Descriptive study. Methods The strategy used from March through December 2020 to upskill nurses in an intermediate care unit to administer critical care upon rapid conversion of the intermediate care unit to an intensive care unit for coronavirus disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Although there was debate among the larger critical care community about the best LPV strategies (14), this center was likely biased toward an approach of limiting Vt and Pplat (15). Additionally, there was an intensive effort to upskill the nursing staff to provide critical care (7), to then support the multidisciplinary teamwork that is necessary for highquality ICU care (29)(30)(31). This was complemented by a closed physician staffing model comprising first-call physicians who were managing COVID-19 ARDS almost exclusively during this period (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there was debate among the larger critical care community about the best LPV strategies (14), this center was likely biased toward an approach of limiting Vt and Pplat (15). Additionally, there was an intensive effort to upskill the nursing staff to provide critical care (7), to then support the multidisciplinary teamwork that is necessary for highquality ICU care (29)(30)(31). This was complemented by a closed physician staffing model comprising first-call physicians who were managing COVID-19 ARDS almost exclusively during this period (32).…”
Section: Discussionmentioning
confidence: 99%
“…Nursing and physician staffing characteristics across the three study units are shown in Figure 1 . When the IMCU/ICU was opened, most IMCU nurses were not critical care trained, and this required a training program that has previously been reported ( 7 ). Briefly, training included self-directed learning, skills days targeting critical care competencies, and on-the-job training supervised by experienced critical care nurses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study further highlighted the importance of incorporating technology-based training methods, such as simulation and e-learning, to enhance the effectiveness of upskilling programs. A study by Duffield et al 202026 emphasized the importance of upskilling nurses in leadership and management. The study found that leadership development programs can improve nurses' confidence, communication, and decision-making skills, ultimately improving patient outcomes.…”
mentioning
confidence: 99%